PENERAPAN METODE K-MEANS CLUSTERING UNTUK STOK PENJUALAN SPAREPART SEPEDA MOTOR - Firdaus, Akbar; Sriani, Sriani; Darta, Ali (JOURNAL OF SCIENCE AND SOCIAL RESEARCH, 2025)
Abstract: Availability of motorcycle spare parts in CV. Solid Mandiri Cemerlang must be monitored to avoid product shortages. The problem that occurs in reporting regarding Most of the items purchased by Most of the customers is under control. Processing incoming and outgoing goods that are not processed by the system requires goods management techniques. The more complete the types of spare parts, customer needs will be met. The collection of available spare parts will be divided into several groups to get the spare parts that customers have purchased the most for each transaction. Data mining is sourced from raw database. This causes problems in databases which tend to be dynamic, complete and large. The K-means Clustering algorithm is capable and effective for finding clusters in data. This calculation will determine the number of clusters at the calculation center and the maximum iteration of data that has been entered into the system. The purpose of implementing the K-means algorithm is to find the value of the goods purchased by the majority of customers so that it makes it easier to provide spare parts. The results of the k-means calculation: C1 (high) has 9 items, C2 (low) has 1 items.Keyword: Motorcycle Parts, K-Means, ClusterAbstrak: Ketersediaan suku cadang sepeda motor di CV. Solid Mitra Cemerlang harus dimonitor untuk menghindari kekosongan barang. Masalah yang terjadi dalam pelaporan mengenai Sebagian besar barang yang dibeli oleh Sebagian besar pelanggan menjadi kendali. Mengolah barang masuk dan keluar yang tidak diproses dengan sistem membutuhkan teknik mengelola barang. Semakin lengkap jenis-jenis suku cadang, kebutuhan pelanggan akan terpenuhi. Pengumpulan suku cadang yang tersedia akan dibagi menjadi beberapa kelompok untuk mendapatkan suku cadang yang paling banyak dibeli pelanggan untuk setiap transaksi. Penambangan data bersumber dari basis data mentah. Hal ini menyebabkan masalah dalam database yang cenderung dinamis, lengkap dan besar. Algoritma K-means Clustering mampu dan efektif untuk menemukan cluster dalam data. Pada perhitungan ini akan menentukan jumlah cluster pada pusat perhitungan dan iterasi maksimum data yang telah dimasukkan kedalam sistem. Tujuan dari penerapan algoritma K-means adalah untuk menemukan nilai dari barang yang dibeli oleh Sebagian besar pelanggan sehingga memudahkan untuk menyediakan suku cadang. Hasil perhitungan k-means: C1 (tinggi) ada 9 barang, C2 (rendah) ada 1 barang.Kata kunci: Suku Cadang Sepeda Motor, K-Means, Cluster